2020
DOI: 10.1002/anie.202010631
|View full text |Cite
|
Sign up to set email alerts
|

The 2‐Pyridyl Problem: Challenging Nucleophiles in Cross‐Coupling Arylations

Abstract: Xinlan Cook received her MChem degree from the University of York in 2017, completing her master's thesis during ayear-long placementa tF.Hoffmann-La Roche (Basel, Switzerland),synthesising novel molecules for the treatment of Alzheimer's disease. She is now completing her doctoral research in the group of Prof. M. C. Willis at the University of Oxford, investigating novel reagents for C(sp 2 )ÀC(sp 2 )d esulfinative cross-coupling reactions. Antoine de Gombert graduated from Chimie ParisTech and UniversitØ Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 274 publications
(114 reference statements)
0
72
0
1
Order By: Relevance
“…Around the same time, Yoshida and Tsuchimoto achieved the direct SMC with diverse aryl-B(dan), demonstrating even robust C(aryl)-B(dan) bonds could be smoothly activated without acidic deprotection (Scheme 68).74 The use of KOtBu as a base under anhydrous conditions is also the key to the successful reaction, and11 B NMR experiments revealed that a transmetalation-active borate species was generated only with KOtBu. Synthetic significance of this method was demonstrated by the smooth SMC with -B(dan), which provides convenient and effective solution to "2-pyridyl problem" in the conventional SMC 49. A quite similar SMC was also reported by Mutoh and Saito.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Around the same time, Yoshida and Tsuchimoto achieved the direct SMC with diverse aryl-B(dan), demonstrating even robust C(aryl)-B(dan) bonds could be smoothly activated without acidic deprotection (Scheme 68).74 The use of KOtBu as a base under anhydrous conditions is also the key to the successful reaction, and11 B NMR experiments revealed that a transmetalation-active borate species was generated only with KOtBu. Synthetic significance of this method was demonstrated by the smooth SMC with -B(dan), which provides convenient and effective solution to "2-pyridyl problem" in the conventional SMC 49. A quite similar SMC was also reported by Mutoh and Saito.…”
mentioning
confidence: 66%
“…Borylative substitution of organic halides with (pin)B-B(dan) was found to be also feasible with a copper catalyst; a variety of alkyl, alkenyl, aryl and heteroaryl halides were smoothly coupled with (pin)B-B(dan) to give the respective R-B(dan) in high yields (Scheme 28) 48. Especially, it should be noted that 2-pyridyl-B(dan) obtained by this reaction shows excellent stability toward aqueous work-up and isolation by Florisil column chromatography, being in stark contrast to the well-known instability of its B(OH) 2 -and B(pin)-counterparts 49. Formation of a ring-opened product in the reaction of cyclopropylmethyl bromide would imply that one-electron transfer process is involved in the reaction pathway (Scheme 29), and a proposed catalytic cycle is shown in Scheme 30.…”
mentioning
confidence: 90%
“…This synthetic challenge has been recognised in the literature and it is frequently referred to as the '2-pyridyl problem'. 6 Professor Leonori said: "I learned about the difficulties in making and handling 2-borylated pyridines and other azines while I was working with Prof. Varinder Aggarwal in Bristol (UK). Indeed, one of the projects I contributed to was aimed at the development of novel transition-metal-free cross-couplings between C2-lithiated pyridines and alkyl boronic esters.…”
Section: A161mentioning
confidence: 99%
“…10,11 Despite this, many synthetic methods that are readily deployed using aryl substrates are not easily applied to the synthesis of heterocyclic compounds; a salient example is the poor stability of 2-pyridylboronic acids, such that 'slow release' alternatives such as trifluoroborates or MIDA boronates are required. 12 Here we describe the identification of dinickel(II) species that readily form in catalytic reactions where α-halo-N-heterocycles are present; these are inert towards transmetalation with organoboron and organotin reagents, but undergo reaction with Grignard reagents. These complexes are therefore not competent for Suzuki-Miyaura cross-coupling reactions but do not impede Kumada-Tamao-Corriu crosscoupling reactions.…”
Section: Introductionmentioning
confidence: 99%